2022
DOI: 10.1080/03007995.2022.2043658
|View full text |Cite
|
Sign up to set email alerts
|

Rationale and design of the Brazilian diabetes study: a prospective cohort of type 2 diabetes

Abstract: Background.Optimal control of traditional risk factors only partially attenuates the exceeding cardiovascular mortality of individuals with diabetes. Employment of machine learning (ML) techniques aimed at identi cation of novel features of risk prediction is a compelling target to tackle residual cardiovascular risk.Objective.To identify clinical phenotypes of T2D which are more prone for developing cardiovascular disease. Methods.The Brazilian Diabetes Study is a single-center, ongoing, prospective registry … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 35 publications
(22 reference statements)
0
4
0
Order By: Relevance
“…This analysis included all cohort who ophthalmological examinations, including fundus examination, and had at least two measurements of glycated hemoglobin (HbA1c). The local ethics committee approved the study (CAEE: 89525518.8.1001.5404), and all patients signed an informed consent form and signed an informed consent form 10 .…”
Section: Methodsmentioning
confidence: 99%
“…This analysis included all cohort who ophthalmological examinations, including fundus examination, and had at least two measurements of glycated hemoglobin (HbA1c). The local ethics committee approved the study (CAEE: 89525518.8.1001.5404), and all patients signed an informed consent form and signed an informed consent form 10 .…”
Section: Methodsmentioning
confidence: 99%
“…8 Participants of the control group were consecutively recruited from an ongoing, local cohort of type 2 diabetes held by our research center, and their selection prioritized patients of similar age and sex as reported in the kidney failure group. 9…”
Section: Study Populationmentioning
confidence: 99%
“…On this occasion, patients underwent SBP measurement [23], ophthalmological examination [24], and peripheral blood and urine sample collection for biochemical analysis. The study design has been detailed elsewhere [25].…”
Section: Study Populationmentioning
confidence: 99%